2014
DOI: 10.1007/s10266-014-0170-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between masticatory performance using a gummy jelly and food intake ability in Japanese complete denture wearers

Abstract: Twenty patients wearing complete dentures were asked to chew a gummy jelly, and their glucose extraction was measured. Two types of masticatory scores (MS1 and MS2) were calculated using a food intake questionnaire. The relationship between masticatory scores and glucose extraction was investigated. The values of masticatory scores were large when the amount of glucose extraction was also large, and there were significantly positive correlations between the two. There was also a positive correlation between MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 13 publications
2
21
0
1
Order By: Relevance
“…The association of an improved masticatory performance with food acceptability can be seen in removable denture patients, especially in edentulous. This shows the positive effect of an improved masticatory function and was in accordance with the study by Shiga et al [19], which found an association between improvements in the food acceptability and masticatory performance after denture treatment. It was also emphasized that a patient's texture acceptability is important for their perceived mastication, which helps them maintain and recover their masticatory performance [32].…”
Section: Correlations Between Assessmentssupporting
confidence: 92%
See 3 more Smart Citations
“…The association of an improved masticatory performance with food acceptability can be seen in removable denture patients, especially in edentulous. This shows the positive effect of an improved masticatory function and was in accordance with the study by Shiga et al [19], which found an association between improvements in the food acceptability and masticatory performance after denture treatment. It was also emphasized that a patient's texture acceptability is important for their perceived mastication, which helps them maintain and recover their masticatory performance [32].…”
Section: Correlations Between Assessmentssupporting
confidence: 92%
“…One of the most widely recognized objective assessments is the masticatory performance (MP), which demonstrates a patient's ability to comminute a specific type of food during mastication. Several methods such as sieving [17], color-changeable chewing gum [18] and gummy jelly [19] have been used for such assessments. Notably, masticatory performance assessment by using gummy jelly [19][20][21][22][23] was widely used as a diagnostic tool due to its fast, easy and accurate application, which is beneficial in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It remains unclear how masticatory ability affects the nutritional status. The relationship of subjective satisfaction with masticatory ability and objective masticatory ability (assessed via masticatory efficiency tests) in older individuals is inconclusive, with previous studies showing either a significant positive correlation [ 9 ] or the lack of a correlation [ 10 ]. In our own clinical observations, we have found that patients may be subjectively satisfied with their masticatory ability despite having a low masticatory efficiency; conversely, other patients may be dissatisfied despite having a high masticatory efficiency.…”
Section: Introductionmentioning
confidence: 99%